Juvenile diabetes, its’ pervasiveness, and actionplan for determent - Sinha, Susmita; Haque, Mainul (Bangladesh Journal of Medical Science, 2023)
In Bangladesh, diabetes mellitus is a substantial public health concern, and its prevalence is rising steadily. Many other mechanisms can cause diabetes in childhood; most children develop type 1 diabetes mellitus primarily due to immune system-mediated β cell death, while type 2 diabetes mellitus is characterized by insulin resistance-related β cell failure. The long-term effects of micro and macrovascular illnesses impose a tremendous strain on those frequently affected early in middle age. The increased prevalence of diabetes in children and the excessive morbidity linked to its effects highlight the significance of preventive measures for future generations. It is essential to look into the possibilities for improvement in school-oriented diabetes management interventions. Consistent engagement and communication on diverse theoretical concepts, performing exploratory assessments to guide interventions, and conducting an operational valuation are necessary to enhance these programs. Furthermore, it is required to identify the significant challenge of the general food milieu and its influence on children’s diets with more participation from related parties like families, stores, and supermarkets. The fast urbanization of Bangladesh may affect the local population’s way of living, there may be a genetic predisposition to diabetes in the country, or both could be responsible for the growth in childhood diabetes mellitus. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 249-255